Analisis Perubahan Material Struktur Terhadap Simpangan Antar Lantai Pada Toko dan Restoran Di Jalan Semer, Kerobokan, Badung - Diatmika, Pande Gede Bayu Guna; Sinarta, I Nengah; Rahadiani, Anak Agung Sagung Dewi (Fakultas Teknik, Universitas Wiraraja, 2025)
The construction project of the store and restaurant in Semer Street, Kerobokan, Badung has changes in some of the structural elements which previously used steel structure to concrete structure. The author chooses to use concrete for the main and sub-structure, while the steel was maintained for the upper structure. The purpose of the analysis are can be able to design the structure of the store and restaurant building that has a strenght plan greater than or equal magnitude of the ultimate force that occurs and also to find out the comparison of story drift between the exsisting and planned building. Analytical method is using study literature on it’s planning by collecting data that related to the plan such as architectural data and soil data. Based on the result of the structural analysis it can be concluded that the control of structural elements has met the standard and on both model where in the story drift have a reduction in deflection due to the material used. The greatest reduction of story drift for Y direction is 61% on the 4th floor and for X direction is 36% on the 1st floor.